32+4c(c-1)=(4c+5c)

Simple and best practice solution for 32+4c(c-1)=(4c+5c) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 32+4c(c-1)=(4c+5c) equation:


Simplifying
32 + 4c(c + -1) = (4c + 5c)

Reorder the terms:
32 + 4c(-1 + c) = (4c + 5c)
32 + (-1 * 4c + c * 4c) = (4c + 5c)
32 + (-4c + 4c2) = (4c + 5c)

Combine like terms: 4c + 5c = 9c
32 + -4c + 4c2 = (9c)
32 + -4c + 4c2 = (9c)

Solving
32 + -4c + 4c2 = (9c)

Solving for variable 'c'.

Reorder the terms:
32 + -4c + (-9c) + 4c2 = (9c) + (-9c)

Combine like terms: -4c + (-9c) = -13c
32 + -13c + 4c2 = (9c) + (-9c)

Combine like terms: (9c) + (-9c) = 0
32 + -13c + 4c2 = 0

Begin completing the square.  Divide all terms by
4 the coefficient of the squared term: 

Divide each side by '4'.
8 + -3.25c + c2 = 0

Move the constant term to the right:

Add '-8' to each side of the equation.
8 + -3.25c + -8 + c2 = 0 + -8

Reorder the terms:
8 + -8 + -3.25c + c2 = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -3.25c + c2 = 0 + -8
-3.25c + c2 = 0 + -8

Combine like terms: 0 + -8 = -8
-3.25c + c2 = -8

The c term is -3.25c.  Take half its coefficient (-1.625).
Square it (2.640625) and add it to both sides.

Add '2.640625' to each side of the equation.
-3.25c + 2.640625 + c2 = -8 + 2.640625

Reorder the terms:
2.640625 + -3.25c + c2 = -8 + 2.640625

Combine like terms: -8 + 2.640625 = -5.359375
2.640625 + -3.25c + c2 = -5.359375

Factor a perfect square on the left side:
(c + -1.625)(c + -1.625) = -5.359375

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| e^4x=25 | | 2/3×2/10= | | 4x-8=12+13x | | a/b-c/b=1 | | F(34)=5x-3 | | -2/5y=15 | | 6x^2+11x=13 | | 5*(-9)= | | 2ln(2x+5)=9 | | (-5)*(-9)= | | (49/s^10)^1/2 | | (-3)+(12)= | | -1=1/4s | | 15x^2+x+8=0 | | 6x-12-4x=6x+7 | | x/8-9=3 | | x(-9)=(-45) | | -37=8x-139 | | 4x+3=-2x+5 | | z/8-9=3 | | (-45)/(-9)= | | 1Log+5= | | 3+2(2x+6)-x= | | 2pq^2-12pq+6q^2-36q= | | 1(5b+11)=19 | | 39+9x=75 | | -2sin^2(x)+sin(X)+2=0 | | 5(2x+7)=10(x-3) | | -2sin^2(x)+sin(X)-2=0 | | 92=4+6(-6-4) | | 160+(x+80)=240 | | 8n+9=n+5 |

Equations solver categories